Umstrittene Vergangenheit Historische Argumente in der Auseinandersetzung Augustins mit den Donatisten - Hogrefe, Arne (Millennium-Studien / Millennium Studies, 2009)
The struggle with the Donatists in North Africa dominated Augustine`s term of office as bishop. In order to disprove their views, in his writings not only did he employ theological arguments, he also referred to events which occurred at the time of the origins of the schism. Augustine`s aim was to use historical documents to prove that the Donatists had no right to claim that they represented the pure Church, free of "traditores". The Donatists reacted to this challenge by developing their own version of the history of the schism. This study draws on Augustine`s anti-Donatist writings to analyse and assess the historical arguments and views of both groups.